Co-Administration of Vonoprazan, Not Tegoprazan, Affects the Pharmacokinetics of Atorvastatin in Healthy Male Subjects - Hwang, Sejung; Ko, Jae-Wook; Lee, Heechan; Kim, Seokuee; Kim, Bongtae; Song, Geun Seog; Kim, Jungryul (Frontiers in Pharmacology, 2021)
Potassium-competitive acid blocker is a new class of drugs inhibiting gastric acid. It is controversial that vonoprazan showed the inhibitory activities of cytochrome P450 3A4. This study aimed to evaluate the pharmacokinetics (PK) of atorvastatin and safety when atorvastatin was administered alone and co-administered with vonoprazan or tegoprazan. An open-label, multiple-dose, 3-intervention, 4-sequence, 4-period, partial replicate crossover study was conducted, and three interventions were; one is orally administered atorvastatin 40 mg alone once daily for seven days, another is atorvastatin co-administered with vonoprazan 20 mg, and the other is atorvastatin co-administered with tegoprazan 50 mg. PK blood samples were collected up to 24 hours after the last dose, and PK parameters for atorvastatin, 2-hydroxyatorvastatin and atorvastatin lactone were estimated by a non-compartmental method. Safety was evaluated, including adverse events and clinical laboratory tests. A total of 28 subjects completed the study. When atorvastatin was co-administered with vonoprazan, the systemic exposures of atorvastatin and atorvastatin lactone significantly increased, and the metabolic ratio of 2-hydroxyatorvastatin significantly decreased. Hypergastrinemia only occurred when atorvastatin was co-administered with vonoprazan. However, the plasma concentration profiles of atorvastatin, 2-hydroxyatorvastatin and atorvastatin lactone were similar when atorvastatin was administered alone or co-administered with tegoprazan. In conclusion, after multiple doses of atorvastatin co-administered with vonoprazan in healthy subjects, the systemic exposure of atorvastatin and the incidence of hypergastrinemia increased. With tegoprazan, however, those interactions were not observed.